Synthesis of Hollow Carbon Fiber from Acacia Leaves (Acacia mangium Willd) as Low Cost Biosorben - Mayrizki, Maura; Darmayanti, Lita; Yenie, Elvi (EduChemia: Jurnal Kimia dan Pendidikan, 2023)
Acacia leaves have a cellulose, hemicellulose, and lignin content of 50.77%. The high content of cellulose can help the formation of hollow fiber structures. The hollow fiber structure makes it possible to carry out greater absorption. This study aims to determine the influence of chemical activator concentration and temperature on the physical activation of hollow carbon fiber characteristics and their ability to adsorb Fe. The synthesis of hollow fiber begins with drying the acacia using sunlight, followed by drying using an oven.  Furthermore, the acacia is grounded and sifted with a 60-mesh sieve. Acacia leaves were chemically activated with concentrations KOH of 0.5, 0.75, and 1 M was carbonized with a temperature of 500°C in a gas environment N2 and continued physical activation with a temperature of 700°C and 750°C using a flow of CO2 gas for 1 hour. The sample was characterized by proximate analysis, SEM, FTIR, and adsorption on Fe. The proximate analysis showed that the water content was 3.5%, ash content was 8.3%, volatile content was 15.4%, and iodine absorption was 761.4 mg/g. The highest Fe metal removal result obtained was 98.8%, with an adsorption capacity of 9,88 mg/g. The results showed that acacia leaf-based hollow carbon fiber has the potential to be an adsorbent to remove ion Fe in solution.